Предмет: Алгебра,
автор: qwertyuioplkkjhhhh
Вычислите:16^-0,125*8^5/6*4^2,5; (2/3)^-3-4^-3
Ответы
Автор ответа:
0
= (2^4)^-0,125 * (2^3)^5/6 * (2^2)^2,5 =
= 2^(4*(-0,125) * 2^(3 * 5/6) *2^(2*2,5) =
=2^(-0,5) * 2^ 2,5 * 2^5 = 2^(-0,5 + 2,5 +5) = 2^7 = 128.
2/3^(-3) - 4^(-2) = (3/2)^3 -(1/4)^2 = 27 / 8 - 1/16=
=(27*2 - 1) / 16 = 53/16
= 2^(4*(-0,125) * 2^(3 * 5/6) *2^(2*2,5) =
=2^(-0,5) * 2^ 2,5 * 2^5 = 2^(-0,5 + 2,5 +5) = 2^7 = 128.
2/3^(-3) - 4^(-2) = (3/2)^3 -(1/4)^2 = 27 / 8 - 1/16=
=(27*2 - 1) / 16 = 53/16
Автор ответа:
0
Спасибо вам огромное
Похожие вопросы